Clinical and Paraclinical Characteristics of Congenital Cholesteatoma in Children Treated at the National ENT Hospital - Anh Tuan, Le; Tuan Son, Nguyen; Hong Anh, Le; Thi Tram Anh, Dang (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 42 No 2, 2026)
Abstract : This retrospective descriptive study aimed to investigate the clinical and paraclinical characteristics of 208 children aged < 6 years who underwent surgery for congenital cholesteatoma at the National ENT Hospital during 2019–2024. The results showed a male predominance (76.4%), with a mean age of 3.02 ± 1.8 years; the 3–4-year age group accounted for the highest proportion (60.1%). Most patients were asymptomatic (85.6%), while 11% had otalgia or otorrhea and only 2.9% had hearing loss. Otoscopic findings indicated that lesions were most commonly located in the anterosuperior quadrant of the tympanic membrane (65.4%), followed by the posterosuperior quadrant (11.5%). Tympanometry results were predominantly type A (83.6%), with type B accounting for 15.9%. Among the 58 ears that underwent preoperative audiometry, the majority had normal hearing (84.5%), with a mean preoperative Pure Tone Audiometry (PTA) of 18.45 ± 9.38 dB and no cases of severe hearing loss. According to Potsic staging, most cases were stage I.  These findings suggest that congenital cholesteatoma in young children typically follows an insidious course with minimal symptoms and is mainly detected incidentally during otoscopic examination. Early diagnosis allows timely intervention when lesions remain localized and hearing function is still largely preserved. Keywords: Congenital cholesteatoma, children, clinical characteristics, paraclinical findings.